Development of information sharing in language neocortex in childhood‐onset drug‐resistant epilepsy. (11th February 2019) - Arya, Ravindra; Ervin, Brian; Wilson, J. Adam; Byars, Anna W.; Rozhkov, Leonid; Buroker, Jason; Horn, Paul S.; Scholle, Craig; Fujiwara, Hisako; Greiner, Hansel M.; Leach, James L.; Rose, Douglas F.; et al.
Summary: Objective: We studied age‐related dynamics of information sharing among cortical language regions with electrocorticographic high‐gamma modulation during picture‐naming and story‐listening tasks. Methods: Seventeen epilepsy patients aged 4‐19 years, undergoing extraoperative monitoring with left‐hemispheric subdural electrodes, were included. Mutual information (MI), a nondirectional measure of shared information, between 16 pairs of cortical regions of interest, was computed from trial‐averaged 70–150 Hz power modulations during language tasks. Impact of age on pairwise MI between language regions and their determinants were ascertained with regression analysis. Results: During picture naming, significant increase in MI with age was seen between pairwise combinations of Broca's area, inferior precentral gyrus (iPreC), and frontal association cortex (FAC); Wernicke's area and posterior association cortex (PAC); and Broca's and Wernicke's areas. During story listening, significant age‐related increase in MI was seen between Wernicke's area and either Broca's area, FAC, or PAC; and between Broca's area and FAC. Significant impact of baseline intelligence quotient was seen on the relationship between age and MI for all pairs, except between Broca's area and iPreC. The mean MI was higher during naming compared to listening for pairs including iPreC with Broca's area, FAC, or PAC and was lower for pairs of Wernicke's area or PAC with anterior language regions. Significance: Information sharing matures with age "within" frontal and temporoparietal language cortices, and "between" Broca's and Wernicke's areas. This study provides evidence for distinct patterns of developmental plasticity within perisylvian language cortex and has implications for planning epilepsy surgery.